Feasibility study on integrating pv with a wind farm - Khairul Izzudin Sulaiman (2023)
Utilizing renewable sources had always been the favourite alternative in reducing the reliance in coal, with much advances in solar and wind technologies these past few decades. In Malaysia, not much had been done in advancing towards reliance in wind; muchly dua to the fact that Malaysia has lower annual average wind speed compared to other countries